PENGARUH METODE PEMBELAJARAN GAME BASED LEARNING DAN MODIFIKASI MEDIA TERHADAP PENGUASAAN TEKNIK PASSING SEPAK BOLA KAKI BAGIAN DALAM PADA SISWA KELAS V SD N 03 BANJARANYAR KABUPATEN BREBES - Rizkyana, Fian; Rahman, Ramdhani (STKIP Muhammadiyah Kuningan, 2024)
The game-based learning (GBL) learning model is game-based learning that increases student collaboration by involving group discussions and modifying lessons to make them interesting and engaging, thereby encouraging creative and innovative teaching methods. The aim of this research is to determine the effect of game-based learning models and media modifications on mastery of football techniques. This research was conducted at SD Negeri 3 Banjaranyar, Brebes District, Central Java. This research is quantitative research. The population used was 104 students from Classes 1–6. The research sample was 18 students from Class V using a purposive sampling technique. The data collection technique used was a pretest-posttest design. Analysis of this research data uses the t test. The research results show that there is a significant influence between the pretest and posttest of group A and group B on mastery of passing techniques with the results of the paired sample t-test with a sig value. (2-tailed), respectively 0.000 (p < 0.05) and 0.000 (p < 0.05). The modified media learning model has a better effect than game-based learning, with the results of the independent sample t-test obtaining a Sig (2-tailed) value of 0.018 < 0.05.